Effects of Aldosterone, Osteoprotegerin and Fibroblast Growth Factor-23 and Some Biochemical Markers in Chronic Kidney Disease Patients (Stage II-IV) among Patients with or without Cardiovascular Events - Ameen, Zeyad A.; Ali, Shatha H. (Iraqi Journal of Pharmaceutical Sciences, 2018)
Chronic Kidney Disease (CKD) is a public health problem and many studies support the link between kidney dysfunction and cardiovascular events. Aldosterone has been shown for decades that a plasma aldosterone concentration is elevated in CKD. Whilst, Osteoprotegerin (OPG), after its capacity to protect bone, also osteoprotegerin is elevated in patients with chronic kidney disease (CKD), where it could predict the deterioration of kidney function, cardiovascular, vascular events and all-cause mortality. On the other hand, fibroblast growth factors (FGFs), in patients with CKD, its levels seem to increase progressively as kidney function worsens. The aim of the present study is to assess the correlations between serum osteoprotegerin, aldosterone and fibroblast growth factor-23 levels in patients with chronic kidney disease stage (II-IV) with and without cardiovascular events.The study includes fifty-nine patients with chronic kidney disease(CKD) and according to CKD-EPI /Creatinine/ 2009 equation to be allocated as stage II-IV, patients were divided into three groups: Group1 (29 patients) with chronic kidney disease(CKD) stage (II-IV) with cardiovascular events. Group2 (30 patients) with chronic kidney disease stage (II-IV) without cardiovascular event, to be compared with Group 3(23 apparently healthy subjects), age and sex matched to that of patients. Serum obtained from their blood specimens to measure; glucose, urea, creatinine, calcium, phosphate, sodium, potassium, aldosterone, FGF-23, Osteoprotergen.Data analysis showed that fasting serum glucose levels of CKD patients (with and without CV disorder) had significantly higher values as compared to the controls (76.5% and 29% respectively).Serum Aldosterone, FGF-23, OPG levels were presented with no significant variation among studied groups with CV events or those without CV events.